PENGEMBANGAN MODEL BIMBINGAN KELOMPOK BERBASIS NILAI KARAKTER LOKAL JAWA UNTUK MENINGKATKAN KESADARAN DIRI (SELF AWARENESS) SISWA. - Noviyanti Kartika Dewi (Universitas PGRI Madiun, 2013)
Self-awareness is the ability of individuals to think of themselves not only as anactor of environmental, but also as an object attention of the others. Based on thepreliminary data the researcher found if the level of self-awareness Junior HighSchool’s student divided into 3 categories, there are high 38.3%, moderate 40%and lower 21.7%. Given the importance of self-awareness to be owned by all thestudents, so it is need necessary to relief efforts to increase self-awareness of thestudents. Which ones effort to help the students increase their self-awareness isoptimize the implementation of guidance group services. Model of guidancegroup based on the value of java local characters can be used as an alternative tomaximize the quality of guidance services